Dorstenia cayapia: aspectos agronômicos - Carvalho, Andre Furtado (2008)
Dorstenia cayapia Vellozo (Carapiá) is a native, shade living and medicinal grass. It belongs to the category "threatened" due to drastic habitat reduction and population decline to a critical level. This work was carried through in glasshouse at Laboratory of Seed Analysis and Experimental Farm of Glória, Uberlândia MG, pertaining to the Center of Agrarian Sciences of the Federal University of Uberlândia and had as objective to get part of agronomic informations that allow to cultivate and explore carapiá rationally permitting at the carapiá specie preservation and attainment of material cultivated for phytotherapeutic products. Three experiments had been carried through: Experiment 1: rhizome prop, Experiment 2: physiological quality of seeds and Experiment 3: plant development came from prop experiment in field. In the rhizome prop Experiment 3, three substrata, three rhizome parts and two types of tray had been evaluated. The delineation was entirely randomized (DIC) in a factorial design (3x3x2). In the experiment of seed physiological quality, the following studies had been carried through: number of seeds by alveolus, degree of humidity, weight of a thousand seeds, seed germination by using different kind of stratum and temperature, electric conductivity, drenching and seed physiological conditioning. The germination assay consisted of two temperatures and three substrata.The delineation used was an entirely randomized design (ERD) in a factorial scheme (3x2). In the electric conductivity, different times of drenching were tested and evaluated through conductive meter readings. The seed drenching consisted of different periods in water contact and these seeds had been used for determination of physiological conditioning. Experiment 3 evaluated the development of sprouted plants came from Experiment 1 in seedbeds under shade plastic sheet by using 20 x 20 cm space during six months. The substrata had not affected the sprouting in trays and in field plant development. The apical part of rizhome sprouting was superior to basal and medium positions. The 128 tray cell was better than in 200 tray cells of rhizome sproutings. The plotting paper substratum and the constant 25 ºC temperature makes possible high seed germination. The electric conductivity can be used to determine the seed vigor of Dorstenia cayapia. The assays of drenching and physiological conditioning had not been significant to improve the indices related with the germination. Six months after transplanting in field, an increasing in relation to plant dry mass taken in tray root was observed, approximately 10 times higher than that produced by underground part and 41 times by aerial part.